Multispacecraft analysis of dipolarization fronts and associated whistler wave emissions using MMS data. Issue 14 (16th July 2016) - Breuillard, H.; Le Contel, O.; Retino, A.; Chasapis, A.; Chust, T.; Mirioni, L.; Graham, D. B.; Wilder, F. D.; Cohen, I.; Vaivads, A.; Khotyaintsev, Yu. V.; Lindqvist, P.‐A.; et al.
Abstract: Dipolarization fronts (DFs), embedded in bursty bulk flows, play a crucial role in Earth's plasma sheet dynamics because the energy input from the solar wind is partly dissipated in their vicinity. This dissipation is in the form of strong low‐frequency waves that can heat and accelerate energetic electrons up to the high‐latitude plasma sheet. However, the dynamics of DF propagation and associated low‐frequency waves in the magnetotail are still under debate due to instrumental limitations and spacecraft separation distances. In May 2015 the Magnetospheric Multiscale (MMS) mission was in a string‐of‐pearls configuration with an average intersatellite distance of 160 km, which allows us to study in detail the microphysics of DFs. Thus, in this letter we employ MMS data to investigate the properties of dipolarization fronts propagating earthward and associated whistler mode wave emissions. We show that the spatial dynamics of DFs are below the ion gyroradius scale in this region (∼500 km), which can modify the dynamics of ions in the vicinity of the DF (e.g., making their motion nonadiabatic). We also show that whistler wave dynamics have a temporal scale of the order of the ion gyroperiod (a few seconds), indicating that the perpendicular temperature anisotropy can vary on such time scales. Key Points: Spatial dynamics of dipolarization fronts are below the ion gyroradius Associated whistler wave dynamics have a temporal scale of the order of the ion gyroperiod The nature of DFs and its implication on associated low‐frequency waves is discussed